Diagnosing variant Creutzfeldt–Jakob disease: a retrospective analysis of the first 150 cases in the UK. Issue 6 (15th December 2010) - Heath, C A; Cooper, S A; Murray, K; Lowman, A; Henry, C; MacLeod, M A; Stewart, G; Zeidler, M; McKenzie, J M; Knight, R S G; Will, R G
Abstract : Introduction: Establishing an early clinical diagnosis in variant Creutzfeldt–Jakob disease (vCJD) can be difficult, resulting in extended periods of uncertainty for many families and sometimes a view that patients have been subjected to unnecessary investigations. This issue is accentuated by the progressive nature of vCJD and by the difficulty in achieving a confident clinical diagnosis before an advanced stage of illness. Although diagnostic delay may be a result of the non-specific early clinical features, a systematic analysis of the process of diagnosis was undertaken, with the aim of trying to achieve earlier diagnosis of vCJD. Methods: Retrospective case file analysis was undertaken of the first 150 definite and clinically probable cases of vCJD identified by the UK surveillance system. Results: There is a significant interval between illness onset and presentation to a primary care physician, which is influenced by the nature of the initial clinical features. Neurological review is invariably sought following the development of clinical signs and a diagnosis is then established relatively quickly. Despite the progressive clinical course, a confident clinical diagnosis is not usually achieved until a relatively advanced stage of illness (mean time to diagnosis 10.5 months) with a more rapid clinical progression accounting for those cases diagnosed earlier after symptom onset. Conclusions: Early clinical diagnosis in vCJD is not possible in the great majority of cases because of non-specific initial symptoms. Once neurological signs develop, a diagnosis is usually made promptly but this is often at a relatively advanced stage of illness. The inherent delays in the diagnosis of vCJD have implications for those involved in both public health and therapeutics.